The Effectiveness of Learning Media as a Supporter of Online Learning in Computer Networking Courses - Novi Hendri Adi; Yera Wahda Wahdi; Ika Parma Dewi; Arina Luthfini Lubis; Army Trilidia Devega (Jurnal Teknologi Informasi dan Pendidikan, 2021)
With the issuance of a study from home policy by the government during the COVID-19 pandemic, the learning process is carried out online. this makes lecturers innovate in using learning media in the learning process. The lack of use of learning media during the COVID-19 pandemic resulted in students being less motivated and having low learning enthusiasm in the computer network learning process. To overcome this problem, one alternative is to develop learning media in the pandemic era. The purpose of this study is to test the effectiveness of the media developed to support the online learning process. The research method of developing learning media used is Research and Development (R&D) using the Instructional Development Institute (IDI) model approach. The IDI approach model includes three stages, namely define, develop, and evaluate. The effectiveness test is carried out at the evaluation stage by treating the control class and the experimental class to students who take computer networking courses using question instruments. The results of this study are the effectiveness of the developed media and can improve student learning outcomes with an average post-test value of 84.78%. By doing this research, it is hoped that students can be motivated and have a passion for learning in the era of the COVID-19 pandemic.